Correlation of the serum cell division cycle 42 with CD4+ T cell subsets and in-hospital mortality in Stanford type B aortic dissection patients - Peng, Hui; Wang, Xugang; Zhang, Longfei; Su, Yang; Yan, Jieli; Wu, Xin (Frontiers in Cardiovascular Medicine, 2024)
Objective Cell division cycle 42 (CDC42) regulates CD4+T-cell differentiation and participates in vascular stiffness and atherosclerosis and is involved in the progression of Stanford type B aortic dissection (TBAD). This study aimed to explore the correlation between serum CDC42 level and CD4+T cell subsets and in-hospital mortality in TBAD patients. Methods Serum CDC42 and peripheral blood T-helper (Th) 1, Th2, and Th17 cells were detected in 127 TBAD patients by enzyme-linked immunosorbent assay and flow cytometry, respectively. Serum CDC42 was also quantified in 30 healthy controls. Results Serum CDC42 was decreased in TBAD patients vs. healthy controls (median [interquartile range (IQR)]: 418.0 (228.0–761.0) pg/ml vs. 992.0 (716.3–1,445.8) pg/ml, P < 0.001). In TBAD patients, serum CDC42 was negatively correlated with Th17 cells (P = 0.001), but not Th1 (P = 0.130) or Th2 cells (P = 0.098). Seven (5.5%) patients experienced in-hospital mortality. Serum CDC42 was reduced in patients who experienced in-hospital mortality vs. those who did not (median (IQR): 191.0 (145.0–345.0) pg/ml vs. 451.5 (298.3–766.8) pg/ml, P = 0.006). By receiver operating characteristic analysis, serum CDC42 showed a good ability for estimating in-hospital mortality [area under curve = 0.809, 95% confidence interval (CI) = 0.662–0.956]. By the multivariate logistic regression analysis, elevated serum CDC42 [odd ratio (OR) = 0.994, 95% CI = 0.998–1.000, P = 0.043] was independently correlated with lower risk of in-hospital mortality, while higher age (OR = 1.157, 95% CI = 1.017–1.316, P = 0.027) was an independent factor for increased risk of in-hospital mortality. Conclusion Serum CDC42 negatively associates with Th17 cells and is independently correlated with decreased in-hospital mortality risk in TBAD patients.